Effects of micro skills training on questioning, explaining, and reinforcement on the clinical instructors' teaching skills - Yanilla, Niña F. (The National Teacher Training Center for the Health Professions, University of the Philippines, Manila, 2013)
This study determined the effects of Micro Skills Training on Questioning, Explaining and Reinforcement (MST-QER) on the clinical instructors' delivery skills. Specifically, it determined and then compared the perceived level of effectiveness and frequency of using the micro skills of questioning, explaining and reinforcement among fifteen clinical instructors (CIs) in Physical Therapy before and after the MST-QER. A quasi-experimental one-group, pretest-posttest design was used. The CIs were given the MST-QER and two weeks later were asked to give their feedback on how the training affected their questioning, explaining, and reinforcement strategies while training interns. A combination of observation, journaling and interviews were done involving their interns too. Quantitative and qualitative analysis included Wilcoxon signed rank test, mean, mode and percentage scoring and content analysis respectively. Wilcoxon test (at p = 0.05) results revealed that the CIs improved in the effectiveness of questioning (0.033) and explaining (0.015) particularly in phrasing (0.007), promoting clarity, fluency and pacing (0.014) and by using examples (0.014). The effectiveness of reinforcement yielded no significant differences (0.156). Reinforcement was already effectively used by 67% of the Cis during the pretest and the amount of increase in the posttest was therefore no longer significant. As regards frequency in the use of the micro skills, the Cis improved only in the use of focusing in questioning (0.011) and activity reinforcement (0.011). It can be concluded that MST-QER improved the clinical instructor's effectiveness in the micro skills of questioning, explaining and reinforcement. The reflexive use of these skills also served as ?eye openers? to the first-time instructors. Further studies include lengthening the implementation period and comparing MST-QER with other existing training programs for CIs